NUMERICAL TEST OF LOWER ARM VEHICLE USING FINITE ELEMENT ANALYSIS AND STATISTICAL METHOD (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
The aim of this study to investigate the influencing factors of the lower suspension arm by integrating finite element technique with response surface methodology (RSM). Response surface methodology has been widely used to predict stress von Mises on lower arm systems models. Aluminum alloys (AA7075-T6) are selected as a suspension arm materials. The structural model of the suspension arm was developed utilizing the Solid works. The finite element model and analysis were performed utilizing the finite element analysis code. The finite element model is correlated with design of experiments (DOE) modal test. Influences of the various factors namely; mesh size, load are investigated using RSM. A mathematical prediction model has been developed based on the most influencing factors and the validation simulation analysis proved its adequacy. The results show that there is no abnormality in the methodology adopted (R2 =0.8406). Ratio greater than 4 is desirable; Model’s ratio of 8.183 indicates an adequate signal. The Model F-value of 5.65 implies the model is significant. RSM was used to design the experiments and analyzed the results obtained. RSM aimed towards prediction stress on lower arm through the various factors of the suspension arm geometrical construction.